Experimental Study and Kinetic Modeling of Decoking of Pacol Process Dehydrogenation Catalyst - M. Toghyani; A. Rahimi; M. Mamanpoush; R. Kazemian; A. H. Harandizadeh (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The Pt/γ-Al2O3 catalyst life time was limited by the formation of coke on the external and internal surfaces of catalyst in dehydrogenation reactors. The kinetics of decoking of dehydrogenation catalyst was studied in a pilot scale fixed bed reactor experimentally. The effects of temperature, oxygen concentration and other operating conditions on decoking process were investigated. A kinetic model was deve-loped to describe the decoking of mentioned catalyst. An objective function was defined as the sum of squares of the deviations among the calculated and plant data. Accordingly the appropriate values were found in order to minimize this function. It was concluded that there was a good agreement between simulation results and experimental data. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)